Подготовка будущих турменеджеров: ландшафтно-экологический аспект - Лей, В.А. (Культура народов Причерноморья, 2013)
В статье дано обоснование и представлены разработки маршрутов ландшафтных
экскурсий, предназначенных для формирования у будущих турменеджеров профессионального кругозора,
эколого-натуралистической компетентности, навыков организации увлекательных маршрутов.
Рассмотрен вариант реализации маршрута ландшафтно-экологической экскурсии в практике работы
со студентами. У статті дане обґрунтування й представлені розробки маршрутів ландшафтних екскурсій,
призначених для формування в майбутніх турменеджеров професійного кругозору, еколого-
натуралістичної компетентності, навичок організації захоплюючих маршрутів. Розглянутий варіант
реалізації маршруту ландшафтно-екологічної екскурсії в практиці роботи зі студентами. The article presents the itinerary development of landscape excursions designed to broaden future
tour managers’ professional horizon, environmental and naturalistic competence and skills of organizing
fascinating itineraries. This approach allows us to solve complex problems connected with preserving the
landscape and ecological uniqueness of the Crimea and Sevastopol region.
In Sevastopol Branch of Saratov State Socio-Economic University within the course “Fundamentals of Tourist
Activity” the third-year students majoring in “Hotel and Tourism Business” have an opportunity to participate
in field classes devoted to the study of landscape and ecological specifics, as well as cultural and historical
features of the Sevastopol region. In this connection, the purpose of providing such itineraries is to form
students' comprehensive understanding of the various natural monuments and landscape specifics of Sevastopol.
The author examines a version of the route of landscape and ecological excursions in practice through working
with students. As an example, the information for the university site, prepared by the students majoring in “Hotel
and Tourism Business”, which graphically presents the content and methodology of the developed tour through
the eyes of students, is given in the article.